High-performance silicon carbide ceramic and method for producing the same
Patent Information
- Application Number
- CN202611144265.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-16
AI Technical Summary
对于未改性的纯SiC或无造粒的SiC细粉,其宽带隙半导体特性导致其在低温下电阻极高,难以直接应用闪烧技术,其导通温度通常高达1000℃以上,能耗显著
(1)工艺简单,成本低廉:本发明中SiC造粒粉中的SiC原料和有机粘结剂均已实现商业化,价格低廉,且本发明中电场辅助工艺制备碳化硅陶瓷的过程,无需额外引入或合成昂贵的导电添加剂(如碳纳米管、石墨烯),从而实现了低成本化,且原料造粒改性处理过程采用粉体球磨混合和喷雾造粒工艺,流程简单,操作简便。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to a novel process for preparing high-performance silicon carbide ceramics with high strength, high toughness, and high electrical conductivity, as well as silicon carbide ceramics themselves, belonging to the field of advanced ceramic material preparation technology. Background Technology
[0002] Silicon carbide (SiC) ceramics are key candidate materials for aerospace, nuclear energy, and high-end equipment due to their excellent high-temperature strength, wear resistance, chemical stability, and thermal conductivity. However, SiC is a strongly covalent compound with a low self-diffusion coefficient, making it difficult to sinter and densify. Furthermore, silicon carbide ceramics suffer from high brittleness and low fracture toughness, limiting their applications. In addition, there is an urgent practical need for silicon carbide ceramics with both high mechanical properties and high electrical conductivity in cutting-edge fields such as semiconductor substrates, electromagnetic shielding, and heating elements. Developing silicon carbide ceramics that can overcome the obstacles of high covalent bonds to achieve densification while possessing high strength, high toughness, and high electrical conductivity has become a key technical challenge that urgently needs to be solved in this field.
[0003] Traditional pressureless sintering involves high temperatures (>2100℃), long cycles, and high energy consumption. Hot pressing sintering can appropriately reduce the sintering temperature, but it still requires materials to be held at temperatures above 1900℃ for a long time, resulting in long sintering cycles, high energy consumption, and demanding equipment requirements. Furthermore, due to the large amount of carbon consumed during high-temperature sintering, the prepared silicon carbide ceramics lack electrical conductivity. Discharge plasma sintering of silicon carbide ceramics can further reduce the sintering temperature to 1800℃, but because silicon carbide powder has poor conductivity, the current is mainly conducted through the graphite mold, resulting in a negligible electric field effect in the silicon carbide sample. Moreover, the powder is prone to local overheating during sintering, leading to inhomogeneity within the prepared silicon carbide ceramics. This results in poor overall mechanical and electrical properties of the material, limiting the application of silicon carbide ceramics.
[0004] Electric field-assisted flash sintering is a novel rapid sintering technology that applies a DC or AC electric field to ceramic green bodies to rapidly densify them at temperatures far lower than traditional sintering, effectively suppressing grain growth. However, a key prerequisite for the successful application of this technology is that the green body must possess a certain level of conductivity at the sintering temperature to form a current path. For unmodified pure SiC or ungranulated SiC fine powder, its wide bandgap semiconductor characteristics result in extremely high resistance at low temperatures, making it difficult to directly apply flash sintering technology. Its conduction temperature is typically above 1000℃, leading to significant energy consumption. Existing technologies usually improve the conductivity of the green body by adding conductive phases (such as carbon black, metal powder, and graphene), but these methods are difficult to disperse evenly, costly, and may introduce impurities, damage material purity, or cause microstructure inhomogeneity.
[0005] Therefore, the main problems and defects of the existing technology are: 1) In order to meet the conductivity requirements of electric field assisted sintering, it is often necessary to introduce external conductive additives that may damage the intrinsic properties of the material; 2) The flash sintering start-up temperature of SiC ceramics is still not low enough, and the energy consumption reduction is limited; 3) The process is complicated or the raw material modification cost is high. Summary of the Invention
[0006] The present invention aims to at least partially solve one of the technical problems in the related art.
[0007] The purpose of this invention is to provide a high-performance silicon carbide ceramic and its preparation method. By constructing a uniform and efficient conductive network in situ between SiC particles, the conduction temperature and sintering temperature of the conductive network are significantly reduced, thereby obtaining silicon carbide ceramics with excellent comprehensive properties such as mechanical and electrical properties.
[0008] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a method for preparing silicon carbide ceramics, comprising the following steps: S1. The raw materials containing silicon carbide raw material powder, organic binder and dispersant are mixed by wet ball milling and then spray granulation to obtain silicon carbide granulated powder. S2. The silicon carbide granulated powder is loaded into a mold and pressure is applied to press and shape it to obtain a ceramic green body. S3. The ceramic green body is placed in an electric field-assisted sintering device. Under vacuum or inert atmosphere, pressure is continuously applied. First, the temperature is raised to 400-800°C to decompose the organic binder on the surface of the granulated powder to form a carbon layer, thereby forming a uniform conductive network inside the ceramic green body. Then, a DC electric field is applied, and the current is allowed to pass only through the ceramic green body. The temperature is then raised to 1500-1700°C for sintering. After sintering, the electric field and heating power supply are turned off, and the pressure is released to obtain silicon carbide ceramic material.
[0009] Furthermore, the particle size of the silicon carbide raw material powder is 0.05–50 μm.
[0010] Furthermore, the organic binder is selected from one or more of polyvinyl alcohol, polyethylene glycol, methylcellulose, phenolic resin, and paraffin wax; And / or, based on the total amount of the silicon carbide raw material powder, the organic binder and the dispersant, the amount of the organic binder added is 1 to 10 wt%.
[0011] Furthermore, the dispersant is selected from one or more of ammonium polyacrylate, ammonium polymethacrylate, polyvinylpyrrolidone, ethylene glycol, and propylene glycol; And / or, based on the total amount of the silicon carbide raw material powder, the organic binder and the dispersant, the amount of the dispersant added is 0.1 to 3 wt%.
[0012] Furthermore, the raw material also includes a sintering aid, which is selected from one or more of B and B4C, and the amount of the sintering aid added is 0.1 to 1 wt% of the silicon carbide raw material powder.
[0013] Furthermore, the wet ball milling adopts a planetary ball mill, and the ball milling parameters include: the ball milling medium is anhydrous ethanol, the mass ratio of the ball milling medium to the mixed powder is (1-4):1; the ball-to-material ratio is (2-5):1; the ball milling speed is 200-400 r / min, and the ball milling time is 4-12 h.
[0014] Furthermore, the spray granulation process employs a centrifugal spray dryer, with process parameters including: controlling the inlet air temperature to be 100–250°C, the outlet air temperature to be 70–110°C, the feed rate to be 50–100 kg / h, the atomizing disc rotation speed to be 15000–25000 r / min, and preferably using compressed air as the granulation atmosphere.
[0015] Furthermore, in step S2, the mold is a cylindrical mold, the pressure is axial pressure, the pressure magnitude is 20-80 MPa, and the pressure holding time is 5-10 min.
[0016] Furthermore, the electric field-assisted sintering device includes a first pressure head, a second pressure head, an annular inner liner, and insulating paper. The first and second pressure heads are spaced apart along a first direction. The annular inner liner at least partially surrounds the first and second pressure heads. The insulating paper is located between the annular inner liner and the first and second pressure heads, forming a sintering cavity between the insulating paper, the first pressure head, and the second pressure head. The insulating paper includes a first surface and a second surface facing each other. The first surface faces and abuts against the annular inner liner, and the second surface faces and abuts against the first and second pressure heads. Further, the thickness of the insulating paper is 0.1–4 mm. The device also includes an annular sleeve located on the side of the annular inner liner away from the sintering cavity, at least partially surrounding the annular inner liner. The first pressure head, the second pressure head, the annular sleeve, and the annular inner liner are all made of graphite or composite graphite material.
[0017] Furthermore, in step S3, the pressure is axial pressure, and the pressure magnitude is 20-80 MPa; And / or, the electric field strength of the DC electric field is 50–500 V / cm, and the upper limit of the current density is controlled to be 20–50 mA / mm. 2 ; And / or, the heating rate in the step of heating to 400-800°C is 20-40°C / min; And / or, the heating to 1500-1700°C includes a first heating stage and a second heating stage, wherein the first heating stage is heating to 1100-1400°C at a rate of 15-40°C / min, and the second heating stage is heating to 1500-1700°C at a rate of 5-15°C / min.
[0018] In a second aspect, the present invention provides silicon carbide ceramics prepared by the method described in any of the preceding claims.
[0019] The above-described technical solution of the present invention has the following advantages: (1) Simple process and low cost: The SiC raw materials and organic binders in the SiC granulation powder of this invention have been commercialized and are inexpensive. In addition, the process of preparing silicon carbide ceramics by electric field assisted process in this invention does not require the introduction or synthesis of expensive conductive additives (such as carbon nanotubes and graphene), thus achieving low cost. Furthermore, the raw material granulation and modification process adopts powder ball milling and spray granulation process, which is simple and easy to operate.
[0020] (2) It can realize the densification sintering of silicon carbide powder under low temperature and short time conditions, and the energy saving effect is significant: In this invention, the carbon layer formed by the decomposition of organic matter on the surface of granulated powder at a low temperature (such as 500℃) can quickly build a conductive network, so that the green body can conduct current at a temperature far below the intrinsic conduction temperature of pure SiC (>1000℃). As the temperature continues to rise, under the synergistic effect of the conductive network and the electric field, the green body resistance drops sharply, the current increases rapidly, and a significant Joule heating effect is generated, thus achieving densification. Therefore, under the conditions of 1650℃ and axial pressure of 40 MPa, dense SiC ceramics can be obtained in only 1 to 2 hours of sintering, which is far lower than the sintering temperature and cycle in the traditional SiC ceramic preparation process, and the energy consumption is greatly reduced.
[0021] (3) Significantly improved performance of silicon carbide ceramic products: In this invention, the carbon layer formed by in-situ pyrolysis originates from the uniform coating on the particle surface. The organic layer on the surface of the granulated powder pyrolyzes to form a continuous or quasi-continuous carbon layer. This carbon layer forms a conductive network between adjacent SiC particles. Therefore, the conductive network is uniformly distributed, which is beneficial to the uniformity of heat distribution during sintering, reduces thermal stress, and significantly improves the uniformity of the microstructure of the sintered body. As a result, the prepared SiC ceramics not only have high density but also outstanding mechanical properties, with a bending strength of 510–660 MPa and a fracture toughness of 4.00–5.50 MPa·m. 1 / 2 Its resistivity is 0.11–9.87 Ω·cm, which is significantly better than that of SiC ceramics prepared by traditional sintering methods at the same temperature.
[0022] (4) Synergistic effect of in-situ conductive network and trace solid-state sintering aid: This invention utilizes the in-situ pyrolysis carbon network to greatly reduce the threshold for electric field conduction and flash burn-in. On this basis, only a trace amount (about 1%) of solid-state sintering aid (such as B4C) is needed to further reduce grain boundary energy, promote grain boundary diffusion, and eliminate residual porosity in the extremely high energy state after flash burn-in. This synergistic mechanism not only preserves the high-purity intrinsic characteristics of SiC materials, but also breaks through the bottleneck of ultra-low temperature densification of strong covalent bond materials, which is the key to achieving high strength and high toughness core performance.
[0023] Meanwhile, the novel synthesis method for SiC ceramic preparation involved in this invention is simple in process, easy to operate and master, highly practical, low in cost, and significantly shortens the cycle time, which is beneficial for industrial production. This invention greatly improves the feasibility of stable preparation of high-performance silicon carbide ceramics, effectively enhances the comprehensive mechanical and electrical properties of the material, and helps to realize the development and application of high-performance silicon carbide ceramics in aerospace, nuclear energy, high-end equipment and other fields. Attached Figure Description
[0024] Figure 1 This is a scanning electron microscope (SEM) image of the fracture morphology of SiC ceramic prepared in Example 1 of this invention.
[0025] Figure 2 This is the sintering shrinkage curve of Example 1.
[0026] Figure 3 This is the sintering shrinkage curve of Comparative Example 1. Detailed Implementation
[0027] As described in the background section, given the high energy consumption and long preparation cycle caused by the high temperature required in the current mainstream SiC sintering process, the lack of conductivity, or poor overall performance due to internal inhomogeneity of the ceramic, and the technical challenges of introducing conductive phase additives in novel flash sintering technologies which may reduce the intrinsic properties of SiC ceramics, it is particularly important to develop a preparation process for high-performance silicon carbide ceramics with low energy consumption, short preparation cycle, and high strength, high toughness, and high conductivity.
[0028] In view of this, in the first part, the present invention provides a method for preparing silicon carbide ceramics, comprising the following steps: S1. The raw materials containing silicon carbide raw material powder, organic binder and dispersant are mixed by wet ball milling and then spray granulation to obtain silicon carbide granulated powder. S2. The silicon carbide granulated powder is loaded into a mold and pressure is applied to press and shape it to obtain a ceramic green body. S3. The ceramic green body is placed in an electric field-assisted sintering device. Under vacuum or inert atmosphere, pressure is continuously applied, and the temperature is first raised to 400-800°C to decompose the organic binder on the surface of the granulated powder to form a carbon layer, thereby forming a uniform conductive network inside the ceramic green body. Then, a DC electric field is applied, and the current is allowed to pass only through the ceramic green body. The temperature is then raised to 1500-1700°C for sintering. After sintering, the electric field and heating power supply are turned off, and the pressure is released to obtain silicon carbide ceramic material.
[0029] Based on the above technical solutions, this invention systematically and scientifically granulates and modifies SiC raw material powder, and designs sintering process parameters. This eliminates the need to introduce external conductive additives, enabling the in-situ construction of a uniform and efficient conductive network between SiC particles. This significantly reduces the conduction temperature of the conductive network and the sintering temperature. Furthermore, the process is simple, has a short preparation cycle, and is inexpensive, thereby greatly lowering the threshold for electric field-assisted sintering. Ultimately, this achieves low-temperature, rapid, and highly dense sintering of SiC ceramics, resulting in excellent comprehensive mechanical and electrical properties.
[0030] In some embodiments of the present invention, the particle size of the silicon carbide raw material powder is 0.05 to 50 μm, including but not limited to 0.1 μm.
[0031] In some embodiments of the present invention, the organic binder is selected from one or more of polyvinyl alcohol (PVA), polyethylene glycol (PEG), methylcellulose, phenolic resin, and paraffin wax, such as polyvinyl alcohol and polyethylene glycol in a mass ratio of 5:4.5 or 4:3.5. The polyvinyl alcohol is selected from any one of polyvinyl alcohols (such as PVA17-88, PVA 17-99, or PVA 24-88) with a degree of polymerization of 1700–2400 and a degree of hydrolysis of 88%–99%. The phenolic resin is selected from any one of thermosetting phenolic resins (such as type 2130) or thermoplastic phenolic resins (such as type 2123). The methylcellulose is selected from any one of methylcelluloses with a 2% aqueous solution viscosity of 400 mPa·s to 4000 mPa·s. The polyethylene glycol is selected from any one of polyethylene glycols (such as PEG-2000, PEG-4000, or PEG-6000) with an average molecular weight of 2000–6000. The paraffin wax is selected from any one of fully refined paraffin waxes (such as 56#, 58#, or 60# fully refined paraffin wax) with a melting point of 54-62℃. Based on the total amount of the silicon carbide raw material powder, the organic binder, and the dispersant, the amount of the organic binder added is 1-10 wt%, such as 1-9.5 wt%, including but not limited to 9.5% and 7.5%. The addition of the organic binder can form a uniform conductive network within the green body after pyrolysis. Insufficient addition leads to uneven distribution, resulting in an uneven microstructure; excessive addition hinders the compact packing of SiC particles. Furthermore, the present invention controls the low addition amount of organic binder (1-10 wt%) because a thinner coating layer is not only sufficient to form a continuous conductive network to induce electric field conduction during the pre-sintering stage, but also effectively controls the residual carbon content inside the final ceramic. Excessive residual carbon not only reduces the intrinsic bulk density of the material but also seriously affects the inherent physicochemical properties of SiC ceramics. By precisely controlling the amount of binder, it is possible to retain the high mechanical strength characteristics of SiC to the maximum extent while ensuring good conductivity.
[0032] In some embodiments of the present invention, the dispersant is selected from one or more of ammonium polyacrylate, ammonium polymethacrylate, polyvinylpyrrolidone, ethylene glycol, and propylene glycol. Based on the total amount of the silicon carbide raw material powder, the organic binder, and the dispersant, the amount of the dispersant added is 0.1–3 wt%, including but not limited to 0.5%. Exemplarily, the weight-average molecular weight of the ammonium polymethacrylate is 10,000–15,000.
[0033] In some embodiments of the present invention, the raw material further includes a sintering aid selected from one or more of B and B4C, and the amount of the sintering aid added is 0.1 to 1 wt% of the silicon carbide raw material powder, including but not limited to 1%. The addition of the sintering aid further helps to promote grain boundary diffusion and eliminate residual porosity, thereby improving density and mechanical properties.
[0034] In some embodiments of the present invention, the wet ball milling employs a planetary ball mill, and the milling parameters include: anhydrous ethanol as the milling medium; a mass ratio of milling medium to mixed powder of (1-4):1; a ball-to-powder ratio of (2-5):1 (mass ratio); a milling speed of 200-400 r / min; and a milling time of 4-12 h. Under these milling parameters, the raw materials can achieve uniform mixing at the microscopic level through ball milling. As an example, the ratio of anhydrous ethanol to mixed powder is 2:1, the ball-to-powder ratio is 3:1, the milling speed is 300 r / min, and the milling time is 4 h.
[0035] In some embodiments of the present invention, the spray granulation process employs a centrifugal spray dryer, with process parameters including: controlling the inlet air temperature at 100–250°C, the outlet air temperature at 70–110°C, the feed rate at 50–100 kg / h, and the atomizing disc rotation speed at 15,000–25,000 r / min; preferably, the granulation atmosphere is compressed air. Materials not treated by spray granulation cannot form a uniform organic coating layer on the surface of spherical particles, resulting in an uneven microstructure within the ceramic. Furthermore, by controlling these process parameters, the particle size and conductive network density of the silicon carbide granulated powder can be adjusted within a suitable range. As an example, the inlet air temperature is controlled at 120°C, the outlet air temperature at 80°C, the feed rate at 50 kg / h, and the atomizing disc rotation speed at 20,000 r / min.
[0036] In some embodiments of the present invention, in step S2, the mold is a cylindrical mold, the pressure is an axial pressure of 20–80 MPa, and the holding time is 5–10 min, such as applying an axial pressure of 40 MPa and holding for 5 min. It is understood that, based on the apparatus used in step S3, the mold can directly be a graphite electric field-assisted hot pressing sintering mold with a cylindrical inner cavity, wherein a boron nitride (BN) insulating layer is used to isolate the sample from contact with the inner liner wall and to prevent current from passing through the mold, for example, with a thickness of 0.2 mm.
[0037] Unlike traditional sintering processes, especially discharge plasma sintering, this invention employs an electric field-assisted sintering device. On one hand, the conductive network formed by pyrolysis creates a circuit path, which significantly reduces the conduction temperature of the conductive network and the sintering temperature. The sintering temperature can be reduced to 1650℃, avoiding the poor conductivity caused by the large consumption of carbon during high-temperature sintering. On the other hand, the current only passes through the ceramic green body, resulting in uniform sintering and a uniform internal structure, thus obtaining silicon carbide ceramic materials with excellent comprehensive mechanical and electrical properties.
[0038] In some embodiments of the present invention, the electric field-assisted sintering apparatus can be any device capable of allowing current to pass only through the ceramic green body. Exemplarily, the electric field-assisted sintering apparatus includes a first pressure head, a second pressure head, an annular liner, and insulating paper. The first and second pressure heads are spaced apart along a first direction. The annular liner at least partially surrounds the first and second pressure heads. The insulating paper is located between the annular liner and the first and second pressure heads, forming a sintering cavity between the insulating paper, the first pressure head, and the second pressure head. The insulating paper includes opposing first and second surfaces. The first surface faces and abuts against the annular liner, and the second surface faces and abuts against the first and second pressure heads. By providing insulating paper between the annular liner and the first and second pressure heads, insulation is achieved between the annular liner and the first and second pressure heads, thereby allowing the first and second pressure heads to conduct only through the material within the sintering cavity.
[0039] Furthermore, the roughness of the first surface is greater than that of the second surface. By making the roughness of the first surface greater than that of the second surface, the connection stability between the annular inner liner and the insulating paper is improved when the first pressure head, the second pressure head and the insulating paper move relative to each other, and the probability of the insulating paper falling off the annular inner liner and causing insulation failure is reduced.
[0040] Furthermore, the thickness of the insulating paper is 0.1–4 mm. The insulating paper can be boron nitride fiber paper, alumina fiber paper, or fiber paper made of other insulating materials.
[0041] Furthermore, the device also includes an annular sleeve located on the side of the annular liner facing away from the sintering cavity, the annular sleeve at least partially surrounding the annular liner.
[0042] Furthermore, the first pressure head, the second pressure head, the annular sleeve, and the annular liner are all made of graphite or composite graphite materials.
[0043] As an example, the present invention uses the electric field-assisted sintering apparatus disclosed in CN 221717308 U.
[0044] In some embodiments of the present invention, in step S3, the pressure is an axial pressure, with a magnitude of 20–80 MPa, such as 40 MPa, and this pressure is maintained throughout the entire heating and sintering process, for example, for a holding time of 5–15 minutes. The sintering atmosphere can be a vacuum or an inert atmosphere, such as argon, nitrogen, or a mixture thereof. Applying a DC electric field can induce a flash burn effect. The electric field strength of the DC electric field is 50–500 V / cm, such as 100 V / cm or 150 V / cm, and the upper limit of the current density is controlled to be 20–50 mA / mm. 2 , such as 40 mA / mm 2 The setting of the electric field strength and current density of the DC electric field is crucial for the stable triggering of the flash burning effect and the Joule heat distribution. The electric field strength provides the driving force to overcome the grain boundary barrier; a suitable electric field can not only promote electron transitions but also induce non-thermal effects such as oxygen vacancy surges. The upper limit of the current density is used to achieve quantitative regulation of energy consumption and stabilize the internal heat generation rate. The synergistic effect of the two ensures the generation of uniform local hot spots inside the green body, promoting grain boundary diffusion and accelerating densification while avoiding local melting or abnormal grain growth caused by current overload, thereby endowing the ceramic with a fine microstructure, high density, and excellent comprehensive properties.
[0045] The heating rate in the step of heating to 400-800℃ is 20-40℃ / min, such as heating to 800℃ at 30℃ / min. The heating to 1500-1700℃ includes a first heating stage and a second heating stage. The first heating stage involves heating to 1100-1400℃ at a rate of 15-40℃ / min, and the second heating stage involves continuing to heat to 1500-1700℃ at a rate of 5-15℃ / min, such as heating to 1300℃ at a rate of 20℃ / min, and then heating to 1650℃ at a rate of 10℃ / min. As the temperature continues to rise, under the synergistic effect of the conductive network and the electric field, the resistance of the billet decreases sharply, the current increases rapidly, and a significant Joule heating effect is generated, achieving densification. The first stage employs a rapid heating rate, utilizing the in-situ carbon mesh to quickly reach the critical conductivity temperature range, significantly shortening the high-temperature exposure time during the non-densification stage. The second stage, approaching the main densification stage, reduces the heating rate to match the transient Joule heating effect during nonlinear current surges, allowing sufficient time for uniform heat conduction and stress release. This design effectively prevents localized thermal stress concentration and sample cracking caused by excessively rapid temperature rise, ensuring the uniformity of the microstructure. It is understood that the method also includes a furnace cooling step to room temperature after depressurization.
[0046] Part Two: This invention provides the silicon carbide ceramic described in any of the preceding claims. The SiC ceramic of this invention has a grain size of approximately 2–3 μm, exhibiting not only high density but also outstanding mechanical properties, with a flexural strength of 510–660 MPa and a fracture toughness of 4.00–5.50 MPa·m. 1 / 2 The resistivity is 0.11–9.65 Ω·cm.
[0047] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some, not all, of the embodiments of this invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0048] The present invention will now be described in further detail with reference to specific embodiments. The given embodiments are merely illustrative of the invention and not intended to limit its scope. The embodiments provided below can serve as a guide for further improvements by those skilled in the art and do not constitute a limitation on the invention in any way.
[0049] Unless otherwise specified, the methods used in the following embodiments are conventional methods, performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Unless otherwise specified, the materials and reagents used in the following embodiments are commercially available.
[0050] The following examples demonstrate the performance testing of the obtained products using conventional testing methods in this industry: In this embodiment, the bulk density was tested according to Archimedes' displacement method (refer to GB / T 25995-2010); the flexural strength was tested by the three-point bending method (span 25 mm, refer to GB / T 6569-2006); the fracture toughness was determined by the single-sided notched beam method (SENB, refer to GB / T 23806-2009); and the room temperature resistivity was determined by the four-probe method or the LCR digital bridge method (refer to GB / T 15662-1995).
[0051] In the following examples, the polyvinyl alcohol (PVA) used is PVA 17-88 with a degree of polymerization of 1700 and a degree of alcoholysis of 88%, the polyethylene glycol (PEG) used is PEG-4000 with an average molecular weight of 4000, and the polymethyl methacrylate uses a polymethyl methacrylate dispersant with a weight average molecular weight of 10000 to 15000.
[0052] Example 1 High-performance silicon carbide ceramic materials were prepared according to the following steps: (1) SiC raw material powder with a particle size of 0.1 μm, binder polyvinyl alcohol (PVA), polyethylene glycol (PEG), and dispersant polymethyl methacrylate were mixed in a mass ratio of 90:5:4.5:0.5. 1% B4C (by weight of silicon carbide powder) was added as a sintering aid. The mixture was ball-milled using a planetary ball mill. The ratio of anhydrous ethanol to the mixed powder was 2:1, the ball-to-powder ratio was 3:1, the ball milling speed was 300 r / min, and the milling time was 4 h. The mixed slurry was then spray-granulated. The inlet temperature was 120 ℃, the outlet temperature was 80 ℃, the feed rate was 50 kg / h, the atomizing disc speed was 20000 r / min, and the granulation atmosphere was compressed air, thereby obtaining granulated modified SiC granulated powder.
[0053] (2) The granulated silicon carbide powder was then loaded into a graphite electric field-assisted hot pressing sintering mold with a cylindrical inner cavity. The BN insulating layer was used to isolate the sample from the inner lining wall, and the thickness was 0.2 mm. An axial pressure of 40 MPa was applied and held for 5 min to ensure that the powder was pressed into shape, thereby obtaining a cylindrical ceramic green body with a diameter of 30 mm and a thickness of about 5 mm.
[0054] (3) The green compact was then placed in an electric field-assisted sintering apparatus. Under a vacuum atmosphere, an axial pressure of 40 MPa was applied and maintained throughout the heating and sintering process. The temperature was first increased to 800 °C at a rate of 30 °C / min to ensure that the organic binder on the surface of the granulated powder was fully decomposed. At the same time, a DC electric field of 100 V / cm was applied, and the upper limit of the current density was set to 40 mA / mm. 2 The temperature was increased to 1300℃ at a rate of 20℃ / min, and then to 1650℃ at a rate of 10℃ / min. After sintering, the electric field and heating power supply were turned off, the pressure was released, and the furnace was cooled to room temperature to obtain silicon carbide ceramic material.
[0055] Figure 1 SEM images show that the sintered body has a dense fracture surface, fine and uniform grains with a grain size of about 2 to 3 μm, and obvious transgranular fracture characteristics. Figure 2 The sintering shrinkage curves show that Example 1 exhibits significant sintering shrinkage during the sintering process. The bulk density of the silicon carbide ceramic material, measured using the Archimedes displacement method, is 3.05 g / cm³. 3 The flexural strength was measured to be 652±658 MPa using the three-point bending method (span 25 mm), and the fracture toughness was measured to be 4.12±0.25 MPa·m using the single-sided notched beam method. 1 / 2 The room temperature resistivity was measured to be 0.17 Ω·cm using the four-probe method.
[0056] Example 2 The difference from Example 1 is that the electric field strength of the DC electric field is adjusted, while the other steps and process parameters are the same as in Example 1.
[0057] High-performance silicon carbide ceramic materials were prepared according to the following steps: (1) SiC raw material powder with a particle size of 0.1 μm, binder polyvinyl alcohol (PVA), polyethylene glycol (PEG), and dispersant polymethyl methacrylate were mixed in a mass ratio of 90:5:4.5:0.5. 1% B4C (by weight of silicon carbide powder) was added as a sintering aid. The mixture was ball-milled using a planetary ball mill. The ratio of anhydrous ethanol to the mixed powder was 2:1, the ball-to-powder ratio was 3:1, the ball milling speed was 300 r / min, and the milling time was 4 h. The mixed slurry was then spray-granulated. The inlet temperature was 120 ℃, the outlet temperature was 80 ℃, the feed rate was 50 kg / h, the atomizing disc speed was 20000 r / min, and the granulation atmosphere was compressed air, thereby obtaining granulated modified SiC granulated powder.
[0058] (2) The granulated silicon carbide powder was then loaded into a graphite electric field-assisted hot pressing sintering mold with a cylindrical inner cavity. The BN insulating layer was used to isolate the sample from the inner lining wall, and the thickness was 0.2 mm. An axial pressure of 40 MPa was applied and held for 5 min to ensure that the powder was pressed into shape, thereby obtaining a cylindrical ceramic green body with a diameter of 30 mm and a thickness of about 5 mm.
[0059] (3) The green compact was then placed in an electric field-assisted sintering apparatus. Under a vacuum atmosphere, an axial pressure of 40 MPa was applied and maintained throughout the heating and sintering process. The temperature was first increased to 800 °C at a rate of 30 °C / min to ensure that the organic binder on the surface of the granulated powder was fully decomposed. At the same time, a DC electric field of 150 V / cm was applied, and the upper limit of the current density was set to 40 mA / mm. 2 The temperature was increased to 1300℃ at a rate of 20℃ / min, and then to 1650℃ at a rate of 10℃ / min. After sintering, the electric field and heating power supply were turned off, the pressure was released, and the furnace was cooled to room temperature to obtain silicon carbide ceramic material.
[0060] The bulk density of the silicon carbide ceramic material, measured using Archimedes' displacement method, was 3.05 g / cm³. 3 The flexural strength was measured to be 623±1 MPa using the three-point bending method (span 25 mm), and the fracture toughness was measured to be 5.05±0.27 MPa·m using the single-sided notched beam method. 1 / 2 The room temperature resistivity was measured to be 9.61 Ω·cm using the four-probe method.
[0061] The process parameters for batching, ball milling, granulation, and pressing of green bodies in Example 2 are the same as in Example 1, except that the electric field strength is changed. This invention adjusts the mechanical and electrical properties of silicon carbide ceramic materials by adjusting the electric field strength of the DC electric field.
[0062] Example 3 The difference from Example 2 is that the mass ratio of SiC raw material powder, binder polyvinyl alcohol (PVA), polyethylene glycol (PEG), and dispersant polyacrylamide is adjusted, while the remaining steps and process parameters are the same as in Example 1.
[0063] High-performance silicon carbide ceramic materials were prepared according to the following steps: (1) SiC raw material powder with a particle size of 0.1 μm, binder polyvinyl alcohol (PVA), polyethylene glycol (PEG), and dispersant polyacrylamide were mixed in a mass ratio of 92:4:3.5:0.5. 1% B4C (by weight of silicon carbide powder) was added as a sintering aid. The mixture was ball-milled using a planetary ball mill. The ratio of anhydrous ethanol to the mixed powder was 2:1, the ball-to-powder ratio was 3:1, the ball milling speed was 300 r / min, and the milling time was 4 h. The mixed slurry was then spray-granulated. The inlet temperature was 120 ℃, the outlet temperature was 80 ℃, the feed rate was 50 kg / h, the atomizing disc speed was 20000 r / min, and the granulation atmosphere was compressed air, thereby obtaining granulated modified SiC granulated powder.
[0064] (2) The granulated silicon carbide powder was then loaded into a graphite electric field-assisted hot pressing sintering mold with a cylindrical inner cavity. The BN insulating layer was used to isolate the sample from the inner lining wall, and the thickness was 0.2 mm. An axial pressure of 40 MPa was applied and held for 5 min to ensure that the powder was pressed into shape, thereby obtaining a cylindrical ceramic green body with a diameter of 30 mm and a thickness of about 5 mm.
[0065] (3) The green compact was then placed in an electric field-assisted sintering apparatus. Under a vacuum atmosphere, an axial pressure of 40 MPa was applied and maintained throughout the heating and sintering process. The temperature was first increased to 800 °C at a rate of 30 °C / min to ensure that the organic binder on the surface of the granulated powder was fully decomposed. At the same time, a DC electric field of 150 V / cm was applied, and the upper limit of the current density was set to 40 mA / mm. 2 The temperature was increased to 1300℃ at a rate of 20℃ / min, and then to 1650℃ at a rate of 10℃ / min. After sintering, the electric field and heating power supply were turned off, the pressure was released, and the furnace was cooled to room temperature to obtain silicon carbide ceramic material.
[0066] The bulk density of the silicon carbide ceramic material, measured using Archimedes' displacement method, was 3.05 g / cm³. 3The flexural strength was measured to be 513±14 MPa using the three-point bending method (span 25 mm), and the fracture toughness was measured to be 5.27±0.25 MPa·m using the single-sided notched beam method. 1 / 2 The room temperature resistivity was measured to be 1.7 Ω·cm using the four-probe method.
[0067] The process parameters for batching, ball milling, granulation, and pressing of green bodies in Example 3 are the same as in Example 2, except for the change in raw material ratio. This invention allows for the adjustment of the mechanical and electrical properties of silicon carbide ceramic materials by modifying the raw material ratio.
[0068] Comparative Example 1 The difference from Example 1 is that step (1) is omitted, and the pure SiC raw material powder is directly subjected to steps (2) and (3), while the process parameters are the same as those in Example 1.
[0069] Silicon carbide ceramic materials were prepared according to the following steps: (1) Pure SiC raw material powder with a particle size of 0.1 μm was loaded into a graphite electric field-assisted hot pressing sintering mold with a cylindrical inner cavity. A BN insulating layer with a thickness of 0.2 mm was used to isolate the sample from the inner lining wall. An axial pressure of 40 MPa was applied and held for 5 min to ensure that the powder was pressed into shape, thereby obtaining a cylindrical ceramic green body with a diameter of 30 mm and a thickness of about 5 mm.
[0070] (2) The green compact was then placed in an electric field-assisted sintering apparatus. Under a vacuum atmosphere, an axial pressure of 40 MPa was applied and maintained throughout the heating and sintering process. The temperature was first increased to 800 °C at a rate of 30 °C / min to ensure that the organic binder on the surface of the granulated powder was fully decomposed. At the same time, a DC electric field of 100 V / cm was applied, and the upper limit of the current density was set to 40 mA / mm. 2 The temperature was increased to 1300℃ at a rate of 20℃ / min, and then to 1650℃ at a rate of 10℃ / min. After sintering, the electric field and heating power supply were turned off, the pressure was released, and the furnace was cooled to room temperature to obtain silicon carbide ceramic material.
[0071] The bulk density of the silicon carbide ceramic material, measured using Archimedes' displacement method, was 2.01 g / cm³. 3 Its structure is loose, making it impossible to conduct effective mechanical performance tests. Figure 3 The sintering shrinkage curves show that Comparative Example 1 did not show significant sintering shrinkage at the same sintering temperature as Example 1.
[0072] The process parameters for Comparative Example 1, including raw material particle size, green pressing process, heating program, sintering temperature, pressure, and electric field strength, were exactly the same as those for Example 1. However, Comparative Example 1 used pure SiC powder without binder granulation modification and without adding sintering aids for direct sintering. The comparison results showed that the silicon carbide ceramic structure obtained by directly sintering pure SiC powder without binder granulation modification and without adding sintering aids was porous. This is because the absence of this step would prevent the achievement of ultra-low temperature densification, which is the key to achieving high strength and high toughness core properties.
[0073] Comparative Example 2 The difference from Example 1 is that in step (1), SiC raw material powder is mixed with superconducting carbon black instead of binder and dispersant, while the remaining steps and process parameters are the same as in Example 1.
[0074] Silicon carbide ceramic materials were prepared according to the following steps: (1) SiC raw material powder with a particle size of 0.1 μm was mixed with 5 wt% superconducting carbon black, and 1% B4C (by weight of silicon carbide powder) was added as a sintering aid. The mixture was ball-milled using a planetary ball mill. The ratio of anhydrous ethanol to mixed powder was 2:1, the ball-to-powder ratio was 3:1, the ball milling speed was 300 r / min, the ball milling time was 4 h, and the mixture was then dried.
[0075] (2) The sample was then placed into a graphite electric field-assisted hot pressing sintering mold with a cylindrical inner cavity. The BN insulating layer was used to isolate the sample from the inner wall and had a thickness of 0.2 mm. An axial pressure of 40 MPa was applied and held for 5 min to ensure that the powder was pressed into shape, thereby obtaining a cylindrical ceramic green body with a diameter of 30 mm and a thickness of about 5 mm.
[0076] (3) The green compact was then placed in an electric field-assisted sintering apparatus. Under a vacuum atmosphere, an axial pressure of 40 MPa was applied and maintained throughout the heating and sintering process. The temperature was first increased to 800 °C at a rate of 30 °C / min to ensure that the organic binder on the surface of the granulated powder was fully decomposed. At the same time, a DC electric field of 100 V / cm was applied, and the upper limit of the current density was set to 40 mA / mm. 2 The temperature was increased to 1300℃ at a rate of 20℃ / min, and then to 1650℃ at a rate of 10℃ / min. After sintering, the electric field and heating power supply were turned off, the pressure was released, and the furnace was cooled to room temperature to obtain silicon carbide ceramic material.
[0077] In this comparative example, due to the tendency of added carbon black to agglomerate, the electric field distribution was extremely uneven, resulting in severe localized melting and large-sized pores inside the sintered body. The measured average bulk density was approximately 2.65 g / cm³. 3 Furthermore, the density varies greatly in different parts, and the bending strength is only 210±45MPa.
[0078] The sintering temperature, pressure, electric field strength, and other process parameters used in Comparative Example 2 were the same as those in Example 1. However, Comparative Example 2 employed a traditional mechanical mixing process with an added conductive phase, replacing the in-situ micro-uniform carbon layer generated by the systematic granulation process in Example 1 with 5% added carbon black. The comparative results showed that the traditional method of improving the conductivity of the green body by adding a conductive phase leads to difficulty in uniformly dispersing the conductive phase, resulting in an uneven microstructure and failing to achieve low-temperature densification.
[0079] Comparative Example 3 The difference from Example 1 is that no DC electric field is applied in step (3), while the remaining steps and process parameters are the same.
[0080] Silicon carbide ceramic materials were prepared according to the following steps: (1) SiC raw material powder with a particle size of 0.1 μm, binder polyvinyl alcohol (PVA), polyethylene glycol (PEG), and dispersant polymethyl methacrylate were mixed in a mass ratio of 90:5:4.5:0.5. 1% B4C (by weight of silicon carbide powder) was added as a sintering aid. The mixture was ball-milled using a planetary ball mill. The ratio of anhydrous ethanol to the mixed powder was 2:1, the ball-to-powder ratio was 3:1, the ball milling speed was 300 r / min, and the milling time was 4 h. The mixed slurry was then spray-granulated. The inlet temperature was 120 ℃, the outlet temperature was 80 ℃, the feed rate was 50 kg / h, the atomizing disc speed was 20000 r / min, and the granulation atmosphere was compressed air, thereby obtaining granulated modified SiC granulated powder.
[0081] (2) The granulated silicon carbide powder is then loaded into a hot press mold with graphite (lined with 0.2 mm graphite paper). An axial pressure of 40 MPa is applied and held for 5 minutes to ensure that the powder is pressed and formed, thereby obtaining a cylindrical ceramic green body with a diameter of 30 mm and a thickness of about 5 mm.
[0082] (3) The green blank is then placed in a conventional hot press furnace, and an axial pressure of 40 MPa is applied under a vacuum atmosphere. This pressure is maintained throughout the heating and sintering process. The temperature is increased to 800°C at 30°C / min, to 1300°C at 20°C / min, and to 1650°C at 10°C / min. After the heating process is completed, the pressure is released and the blank is cooled to room temperature with the furnace.
[0083] The bulk density, measured using Archimedes' displacement method, is only 2.36 g / cm³. 3 This indicates that at a low temperature of 1650℃, without the assistance of an electric field and the excitation of the Joule heating effect, the powder of this formula cannot be densified at all.
[0084] The raw material formulation, granulation process, maximum sintering temperature (1650℃), and pressure parameters used in Comparative Example 3 were exactly the same as those in Example 1, but no DC electric field was applied to induce flash burning in Comparative Example 3. The comparative results show that applying a DC electric field is also a key step in achieving low-temperature densification of the material.
[0085] Comparative Example 4 The difference from Comparative Example 3 is that the sintering temperature is further increased to 1900℃ in step (3), while the remaining steps and process parameters are the same.
[0086] High-performance silicon carbide ceramic materials were prepared according to the following steps: (1) SiC raw material powder with a particle size of 0.1 μm, binder polyvinyl alcohol (PVA), polyethylene glycol (PEG), and dispersant polymethyl methacrylate were mixed in a mass ratio of 90:5:4.5:0.5. 1% B4C (by weight of silicon carbide powder) was added as a sintering aid. The mixture was ball-milled using a planetary ball mill. The ratio of anhydrous ethanol to the mixed powder was 2:1, the ball-to-powder ratio was 3:1, the ball milling speed was 300 r / min, and the milling time was 4 h. The mixed slurry was then spray-granulated. The inlet temperature was 120 ℃, the outlet temperature was 80 ℃, the feed rate was 50 kg / h, the atomizing disc speed was 20000 r / min, and the granulation atmosphere was compressed air, thereby obtaining granulated modified SiC granulated powder.
[0087] (2) The granulated silicon carbide powder is then loaded into a hot press mold with graphite (lined with 0.2 mm graphite paper). An axial pressure of 40 MPa is applied and held for 5 minutes to ensure that the powder is pressed and formed, thereby obtaining a cylindrical ceramic green body with a diameter of 30 mm and a thickness of about 5 mm.
[0088] (3) The green blank is then placed in a conventional hot press furnace, and an axial pressure of 40 MPa is applied under a vacuum atmosphere. This pressure is maintained throughout the heating and sintering process. The temperature is increased to 800°C at 30°C / min, to 1300°C at 20°C / min, to 1650°C at 10°C / min, and to as high as 1900°C at 5°C / min. After holding at this temperature for 2 hours, the pressure is released and the blank is cooled to room temperature with the furnace.
[0089] The bulk density of the silicon carbide ceramic material was measured to be 3.15 g / cm³. 3 The flexural strength is 596±52 MPa, and the fracture toughness is 4.62±0.43 MPa·m. 1 / 2 The room temperature resistivity was measured to be 83800 Ω·cm using the LCR digital bridge method.
[0090] The raw material formulation, granulation process, and pressure parameters used in Comparative Example 4 were the same as those in Example 1. However, Comparative Example 4 employed a traditional high-temperature hot-pressing sintering process without an applied electric field, and its highest sintering temperature reached 1900℃ (far higher than the 1650℃ in Example 1). The comparative results showed that only by significantly increasing the sintering temperature to 1900℃ and holding it at that temperature for 2 hours could the mechanical properties of Example 1 (rapid flash firing at 1650℃) be achieved. This process consumed a huge amount of energy. Furthermore, due to the large amount of carbon consumed during high-temperature sintering, its room temperature resistivity reached as high as 83800 Ω·cm, lacking electrical conductivity and thus preventing the application of high-performance silicon carbide ceramics in the field of electrical conductivity.
[0091] Comparative Example 5 The difference from Example 1 is that in step (2), a graphite SPS mold is used for pressing and forming, and in step (3), a discharge plasma sintering furnace is used for sintering.
[0092] High-performance silicon carbide ceramic materials were prepared according to the following steps: (1) SiC raw material powder with a particle size of 0.1 μm, binder polyvinyl alcohol (PVA), polyethylene glycol (PEG), and dispersant polymethyl methacrylate were mixed in a mass ratio of 90:5:4.5:0.5. 1% B4C (by weight of silicon carbide powder) was added as a sintering aid. The mixture was ball-milled using a planetary ball mill. The ratio of anhydrous ethanol to the mixed powder was 2:1, the ball-to-powder ratio was 3:1, the ball milling speed was 300 r / min, and the milling time was 4 h. The mixed slurry was then spray-granulated. The inlet temperature was 120 ℃, the outlet temperature was 80 ℃, the feed rate was 50 kg / h, the atomizing disc speed was 20000 r / min, and the granulation atmosphere was compressed air, thereby obtaining granulated modified SiC granulated powder.
[0093] (2) The granulated silicon carbide powder is then loaded into a graphite SPS mold (lined with 0.2 mm graphite paper). An axial pressure of 40 MPa is applied and held for 5 minutes to ensure that the powder is pressed and formed, thereby obtaining a cylindrical ceramic green body with a diameter of 30 mm and a thickness of about 5 mm.
[0094] (3) The green blank is then placed in a discharge plasma sintering furnace, and an axial pressure of 40 MPa is applied under a vacuum atmosphere. This pressure is maintained throughout the heating and sintering process. The temperature is increased to 1800°C at 100°C / min, held for 5 minutes, and then the pressure is released and the furnace is cooled to room temperature.
[0095] The bulk density of the silicon carbide ceramic material was measured to be 3.18 g / cm³. 3 The flexural strength is 466±26MPa, and the fracture toughness is 4.28±0.21MPa·m. 1 / 2The room temperature resistivity was measured to be 51600 Ω·cm using the LCR digital bridge method.
[0096] The raw material formulation, granulation process, and pressure parameters used in Comparative Example 5 were the same as those in Example 1. However, Comparative Example 5 employed a discharge plasma sintering process, and its highest sintering temperature reached 1800℃ (higher than 1650℃ in Example 1). This comparative example demonstrates that increasing the discharge plasma sintering temperature results in higher energy consumption and relatively lower flexural strength of the material. Furthermore, due to the significant carbon consumption during high-temperature sintering, its room temperature resistivity reaches as high as 51600 Ω·cm, rendering it non-conductive and unable to achieve the application of high-performance silicon carbide ceramics in conductive fields.
[0097] Comparative Example 6 The difference from Example 1 is that in step (1), the ball milling is followed by direct drying instead of spray granulation, while the remaining steps and process parameters are the same.
[0098] Silicon carbide ceramic materials were prepared according to the following steps: (1) SiC raw material powder with a particle size of 0.1 μm, binder polyvinyl alcohol (PVA), polyethylene glycol (PEG), and dispersant polymethyl methacrylate were mixed in a mass ratio of 90:5:4.5:0.5. 1% B4C (by weight of the silicon carbide powder) was added as a sintering aid. The mixture was ball-milled using a planetary ball mill. The ratio of anhydrous ethanol to the mixed powder was 2:1, the ball-to-powder ratio was 3:1, the ball milling speed was 300 r / min, and the milling time was 4 h. The mixed slurry was then dried.
[0099] (2) The sample was then placed into a graphite electric field-assisted hot pressing sintering mold with a cylindrical inner cavity. The BN insulating layer was used to isolate the sample from the inner wall and had a thickness of 0.2 mm. An axial pressure of 40 MPa was applied and held for 5 min to ensure that the powder was pressed into shape, thereby obtaining a cylindrical ceramic green body with a diameter of 30 mm and a thickness of about 5 mm.
[0100] (3) The green compact was then placed in an electric field-assisted sintering apparatus. Under a vacuum atmosphere, an axial pressure of 40 MPa was applied and maintained throughout the heating and sintering process. The temperature was first increased to 800 °C at a rate of 30 °C / min to ensure that the organic binder on the surface of the granulated powder was fully decomposed. At the same time, a DC electric field of 100 V / cm was applied, and the upper limit of the current density was set to 40 mA / mm. 2 The temperature was increased to 1300℃ at a rate of 20℃ / min, and then to 1650℃ at a rate of 10℃ / min. After sintering, the electric field and heating power supply were turned off, the pressure was released, and the furnace was cooled to room temperature to obtain silicon carbide ceramic material.
[0101] The silicon carbide ceramic exhibited significant microstructural inhomogeneity, with a bulk density of 2.82 g / cm³. 3 Its flexural strength is relatively low (320±60MPa).
[0102] The raw material formulation, sintering temperature, pressure, and electric field strength used in Comparative Example 6 were exactly the same as those in Example 1. However, Comparative Example 6 employed a simple mechanical mixing and drying process, without the crucial spray granulation treatment. The comparative results revealed that the internal microstructure of the ceramic was uneven. This is because omitting the spray granulation step prevented the formation of a uniform organic coating layer on the surface of the spherical particles, further demonstrating the irreplaceable role of spray granulation in constructing a uniform and efficient in-situ conductive network.
[0103] Comparative Example 7 The difference from Example 1 is that the sintering aid B4C is not added.
[0104] Silicon carbide ceramic materials were prepared according to the following steps: (1) SiC raw material powder with a particle size of 0.1 μm, binder polyvinyl alcohol (PVA), polyethylene glycol (PEG), and dispersant polymethyl methacrylate were mixed in a mass ratio of 90:5:4.5:0.5. A planetary ball mill was used for ball milling. The ratio of anhydrous ethanol to mixed powder was 2:1, the ball-to-powder ratio was 3:1, the ball milling speed was 300 r / min, and the ball milling time was 4 h. The mixed slurry was then subjected to spray granulation treatment. The inlet temperature during spray granulation was 120 ℃, the outlet temperature was 80 ℃, the feed rate was 50 kg / h, the atomizing disc speed was 20000 r / min, and the granulation atmosphere was compressed air, thereby obtaining granulated modified SiC granulated powder.
[0105] (2) The granulated silicon carbide powder was then loaded into a graphite electric field-assisted hot pressing sintering mold with a cylindrical inner cavity. The BN insulating layer was used to isolate the sample from the inner lining wall, and the thickness was 0.2 mm. An axial pressure of 40 MPa was applied and held for 5 min to ensure that the powder was pressed into shape, thereby obtaining a cylindrical ceramic green body with a diameter of 30 mm and a thickness of about 5 mm.
[0106] (3) The green compact was then placed in an electric field-assisted sintering apparatus. Under a vacuum atmosphere, an axial pressure of 40 MPa was applied and maintained throughout the heating and sintering process. The temperature was first increased to 800 °C at a rate of 30 °C / min to ensure that the organic binder on the surface of the granulated powder was fully decomposed. At the same time, a DC electric field of 100 V / cm was applied, and the upper limit of the current density was set to 40 mA / mm. 2The temperature was increased to 1300℃ at a rate of 20℃ / min, and then to 1650℃ at a rate of 10℃ / min. After sintering, the electric field and heating power supply were turned off, the pressure was released, and the furnace was cooled to room temperature to obtain silicon carbide ceramic material.
[0107] The measured bulk density was 2.88 g / cm³. 3 The flexural strength is 412±25MPa, and the fracture toughness is 3.35±0.21MPa·m. 1 / 2 .
[0108] The raw material formulation, sintering temperature, pressure, and electric field strength used in Comparative Example 7 were exactly the same as those in Example 1, except that no sintering aid was added. The results showed that the in-situ carbon mesh could successfully induce flash densification, but in the absence of trace amounts of sintering aid to help eliminate residual porosity, the density and mechanical properties were slightly lower than those in Example 1, confirming the necessity of the synergistic effect of the two.
[0109] Comparative Example 8 The difference between Comparative Example 8 and Example 1 is that in step (2), a graphite SPS mold is used for pressing and molding, and in step (3), a discharge plasma sintering furnace is used for sintering, with the maximum sintering temperature set only to 1650°C. The specific steps are similar to those in Comparative Example 5, except that the maximum sintering temperature was lowered from 1800℃ to 1650℃. The bulk density, measured using the Archimedes displacement method, was only 2.61 g / cm³. 3 The flexural strength is only 245±30MPa, making effective fracture toughness testing impossible. The results of Comparative Example 8 further demonstrate that the traditional spark plasma sintering (SPS) process is highly dependent on high temperatures (such as above 1800℃) to obtain dense silicon carbide ceramics. At the same low temperature of 1650℃ as this invention, the SPS process cannot achieve effective densification and excellent mechanical properties.
[0110] The present invention has been described in detail above. Those skilled in the art will recognize that the invention can be implemented in a wide range of ways with equivalent parameters, proportions, and conditions without departing from its spirit and scope. While specific embodiments have been provided, it should be understood that further modifications can be made to the invention. In summary, according to the principles of the invention, this application is intended to include any changes, uses, or improvements to the invention, including modifications made using conventional techniques known in the art that depart from the scope disclosed herein.
Claims
1. A method for preparing silicon carbide ceramics, characterized in that, Includes the following steps: S1. The raw materials containing silicon carbide raw material powder, organic binder and dispersant are mixed by wet ball milling and then spray granulation to obtain silicon carbide granulated powder. S2. The silicon carbide granulated powder is loaded into a mold and pressure is applied to press and shape it to obtain a ceramic green body. S3. The ceramic green body is placed in an electric field-assisted sintering device. Under vacuum or inert atmosphere, pressure is continuously applied. First, the temperature is raised to 400-800°C to decompose the organic binder on the surface of the granulated powder to form a carbon layer, thereby forming a uniform conductive network inside the ceramic green body. Then, a DC electric field is applied, and the current is allowed to pass only through the ceramic green body. The temperature is then raised to 1500-1700°C for sintering. After sintering, the electric field and heating power supply are turned off, and the pressure is released to obtain silicon carbide ceramic material.
2. The method for preparing silicon carbide ceramics according to claim 1, characterized in that, The particle size of the silicon carbide raw material powder is 0.05–50 μm; And / or, the organic binder is selected from one or more of polyvinyl alcohol, polyethylene glycol, methylcellulose, phenolic resin, and paraffin wax; And / or, based on the total amount of the silicon carbide raw material powder, the organic binder, and the dispersant, the amount of the organic binder added is 1 to 10 wt%; And / or, the dispersant is selected from one or more of ammonium polyacrylate, ammonium polymethacrylate, polyvinylpyrrolidone, ethylene glycol, and propylene glycol; And / or, based on the total amount of the silicon carbide raw material powder, the organic binder and the dispersant, the amount of the dispersant added is 0.1 to 3 wt%.
3. The method for preparing silicon carbide ceramics according to any one of claims 1-2, characterized in that, The raw materials also include sintering aids, which are selected from one or more of B and B4C, and the amount of sintering aids added is 0.1 to 1 wt% of the silicon carbide raw material powder.
4. The method for preparing silicon carbide ceramics according to any one of claims 1-3, characterized in that, The wet ball milling process uses a planetary ball mill, and the ball milling parameters include: the ball milling medium is anhydrous ethanol, the mass ratio of the ball milling medium to the mixed powder is (1-4):1; the ball-to-material ratio is (2-5):1; the ball milling speed is 200-400 r / min, and the ball milling time is 4-12 h.
5. The method for preparing silicon carbide ceramic according to any one of claims 1-4, characterized in that, The spray granulation process uses a centrifugal spray dryer, and the process parameters include: controlling the inlet air temperature to be 100-250℃, the outlet air temperature to be 70-110℃, the feed rate to be 50-100kg / h, the atomizing disc rotation speed to be 15000-25000r / min, and preferably using compressed air as the granulation atmosphere.
6. The method for preparing silicon carbide ceramics according to any one of claims 1-5, characterized in that, In step S2, the mold is a cylindrical mold, the pressure is axial pressure, the pressure magnitude is 20-80 MPa, and the pressure holding time is 5-10 min.
7. The method for preparing silicon carbide ceramics according to any one of claims 1-6, characterized in that, The electric field-assisted sintering device includes a first pressure head, a second pressure head, an annular liner, and insulating paper. The first pressure head and the second pressure head are spaced apart along a first direction. The annular liner at least partially surrounds the first pressure head and the second pressure head. The insulating paper is located between the annular liner and the first pressure head and the second pressure head. A sintering cavity is formed between the insulating paper, the first pressure head, and the second pressure head. The insulating paper includes a first surface and a second surface facing each other. The first surface faces the annular liner and abuts against the annular liner. The second surface faces the first pressure head and the second pressure head and abuts against the first pressure head and the second pressure head.
8. The method for preparing silicon carbide ceramics according to claim 7, characterized in that, The thickness of the insulating paper is 0.1–4 mm; The device further includes an annular sleeve located on the side of the annular liner facing away from the sintering cavity, and the annular sleeve at least partially surrounds the annular liner. The first pressure head, the second pressure head, the annular sleeve, and the annular liner are all made of graphite or composite graphite materials.
9. The method for preparing silicon carbide ceramic according to any one of claims 1-8, characterized in that, In step S3, the pressure is axial pressure, and the pressure magnitude is 20-80 MPa; And / or, the electric field strength of the DC electric field is 50–500 V / cm, and the upper limit of the current density is controlled to be 20–50 mA / mm. 2 ; And / or, the heating rate in the step of heating to 400-800°C is 20-40°C / min; And / or, the heating to 1500-1700°C includes a first heating stage and a second heating stage, wherein the first heating stage is heating to 1100-1400°C at a rate of 15-40°C / min, and the second heating stage is heating to 1500-1700°C at a rate of 5-15°C / min.
10. Silicon carbide ceramics prepared by the method of any one of claims 1-9.